FORMATION OF POSITIVE ATTITUDE TO PHYSICAL EDUCATION LESSONS FOR SCHOOLCHILDREN THROUGH THE EDUCATION OF THE MODERN TEACHER - T.V. Andrianov; V.I. Marchyk; V.E. Andrianov (Academy of Cognitive and Natural Sciences, 2004)
It Is Determined that actions, which effectively raise the interest a pupil to physical culture, are found in border professional strong, bright, enthusiastic personality - a teacher of the physical culture, which actively propagandizes the ideas of the physical culture and sport.